PENGARUH PERLAKUAN KIMIAWI TERHADAP PERKECAMBAHAN BENIH PALEM PUTRI - Siti Rosmiati Mutha Kasi; Yosefina lewar; Ali Hasan (Partner, 2017)
Palm is one of the ornamental plants which attracted many people. It is a tropical and subtropical plant which requires full sun. Princess Palm (Veitchia merilli) is one of the most desirable palm and is potential as ornamental plants of high economic value. It  is one of  palm species which is propagated by seed. Seed should germinate quickly in order to get palm seedlings in a short time. Slow germination is an obstacle in the cultivation of palm,  because the palm seed coat is very hard, thus inhibiting seed germination process. This research aimed at determining the influence of chemical treatments on the germination of Princess Palm.  This research was conducted in the screen house of laboratory of horticulture Kupang State Polytechnic of Agriculture between June and August 2015. The research design used in this study was randomized block design (RBD). The treatments used were: no chemical treatment, H2SO4, KNO3 and combination of  H2SO4 and KNO3. The results showed  that the chemical treatment affects the germination and seedling growth of Princess Palm. H2SO4 and KNO3 treatment gives best germination palm especially in terms speed growth and value of germination.  Keywords: Palm, Chemical Treatment, Germination, Seed